Desempenho de um microtrator agrícola em diferentes relações peso e potência - Sombra, Weberte Alan (2013)
The objective of this test is evaluate the energy performance of an agricultural microtractor Yanmar Agritech ® model NSB14S with nominal power of 10.3 kW (14 hp) under three different weight / power ratios, 0.41, 0.54 and 0,67 kN kW-1 (41, 54 e 67 kgf kW-1) in three roller surface (concrete, firm soil and soil disturbed). The assay was performed on three roller surface, a concrete track for testing agricultural machinery, agricultural soil firm track and agricultural mobilized soil track. To obtain data on energy efficiency, the microtractor was instrumented with inductive sensors in the wheels to measure the slipping wheelset, volumetric meters of fuel consumption and load cell for the workforce to the drawbar. The experimental design was used on track. In each lane were disposed the treatments with a factorial arrangement of 3x3, with 6 replicates per lane, totaling 54 experimental units, all data were subjected to analysis of variance, applied the Tukey test at 5% significance for the comparison of measurements. All statistical analyzes were performed with the aid of software ASSISTAT Version 7.6 beta (2012) by Federal University of Campina Grande. The variable displacement speed (km h-1), slipping (%), available power on drawbar (kW) and yield on the drawbar (%), showed a significant interaction, however the variables traction force on drawbar (kN), hourly fuel consumption (L h-1) and specific fuel consumption (g.kWh-1), they had a significant effect only on the variation factor roller surface. Provided that the rate weight/power 41 kW kgf-1, showed higher index of slipping and displacement speed both in mobilized surface. The fuel consumption had showed lower values on concrete surface, to specific fuel consumption the mobilized soil surface showed better energy conversion, as well as improve power on the drawbar. Yields on the drawbar are below the proposed by ASAE.